Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
From stabilization to growth. The Global Policy Agenda (GPA) presented to the IMFC during the 2013 Spring Meetings charted a range of actions needed to invigorate a sustainable recovery and to make the global economy more resilient. The GPA also outlined how the Fund can best assist members in placing the global economy on a sustained and balanced growth path. This work program translates the policy priorities laid out in the GPA into the agenda for the Fund over the next six to twelve months. Progress on commitments outlined at the Spring Meetings will be assessed in the Fall GPA, which will also detail policy directions for the Fund and the membership.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: EME; Fund; Policy Advice; Policy; PP